Réponses

2013-10-16T20:47:09+02:00
A= -2 x [-3-(-2)]
= -2*(-3+2)
=-2*(-5)
=10

B=25 x (-0,5-2)
=25*(-2.5)
= -62.5

C= -50 x (-0,0158) x 25 x (-4) x2
= (25*(-4)*(-50*2)*(-0.0158)
= -100*(-100)*(-0.0158)
=10000*(-0.0158)
= -158

D= -[3,5-(-2)]x(-7-4)
=-(5.5)*(-11)
=5.5*11
=60.5
Meilleure réponse !
2013-10-16T21:05:10+02:00
A = -2 x [ -3 - ( -2 ) ]
= -2 x ( -3 + 2 )
= -2 x( -5 )
= 10

B = 25 x ( -0,5 - 2 )
= 25 x ( -2.5 )
= -62,5

C = -50 x ( -0,0158 ) x 25 x ( -4 ) x2
= ( 25x ( -4 ) x ( -50 x 2 ) x ( -0.0158 )
= -100 x ( -100 ) x ( -0.0158 )
= 10000 x ( -0.0158 )
= -158

Dv= -[ 3,5 - ( -2 ) ] x ( -7-4 )
= -( 5,5) x ( -11 )
= 5,5 x 11
= 60,5